Ethics in forensic social work - McLeod, David Axlyn (Handbook of forensic social work, 2024)
Forensic social workers have been involved in forensic practice for decades, and forensic social workers have different roles and responsibilities in the criminal and civil justice systems. Also, forensic social workers collaborate with various parts and professionals of the legal system throughout the legal process. While collaborating with different facets of the legal system, there could be ethical dilemmas and conflicts between social workers and other professionals. The purpose of ethics is to provide general principles of professional behavior that social workers should follow. The authors of this chapter will explain the differences between ethics and law and the differences between values and ethics. They will discuss social workers’ roles and ethical considerations and their relationship with legal professionals in the criminal justice system and forensic environments. Additionally, they provide information on how forensic social workers can develop a practice of ethical decision-making.